Effect of coffee (Coffea arabica) pulp meal as feed on productive parameters of guinea pigs (Cavia porcellus l) – Peru breed - Yoplac, Ives (2017)
The objective of this study was to determine the effect of feeding guinea pigs (Cavia porcellus L) – Peru breed with coffee (Coffea arabica) pulp meal on productive parameters during the rearing and fattening stages. A total of 35 female guinea pigs were monitored from 28 to 91 days of age, and fed with alfalfa and concentrate (1:1). The animals were randomly distributed in five treatments with inclusions of 0, 5, 15, 25 and 35% of coffee pulp meal in the concentrate. The addition of the coffee pulp meal to the concentrate did not affect body weight gain, feed conversion and sensory quality (appearance, odor, carcass color and meat taste) but had an inverse relationship with feed consumption. The highest carcass yields were obtained with the inclusion of up to 25% of coffee pulp meal in the concentrate. Therefore, coffee pulp meal, as an input to formulate guinea pig concentrates, has the potential to increase the productive performance.